2020
DOI: 10.1002/jmd2.12111
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase deficiency—Clinical insights and a novel deletion in TH gene in an Indian patient

Abstract: Tyrosine hydroxylase deficiency is a rare autosomal recessive, treatable disorder of neurotransmission. Fewer than 100 cases have been reported so far. We present a case of a 10-month-old infant who was symptomatic since 5 months of age and who received an initial diagnosis of infantile tremor syndrome. She presented with rest tremor, decreased facial expression, global hypokinesia, and later on with oculogyric crisis and dystonia. This diagnosis was revised after confirmation of tyrosine hydroxylase deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We compiled the summary from Dong et al, encompassing all TH deficiency cases reported through 2018 (Dong et al, 2020) and all Segawa patients published thereafter until 2023 (Atanasoska et al, 2023; Bijarnia‐Mahay et al, 2020; Champagne et al, 2022; Chen et al, 2020; Couto et al, 2019; Hou et al, 2019; Hull et al, 2021; Janssen et al, 2021; Kuseyri Hubschmann et al, 2021; Panda et al, 2022; Reyes et al, 2023; Wang et al, 2022). In total, we summarized the clinical phenotypes of all 175 reported Segawa cases.…”
Section: Case Presentationmentioning
confidence: 99%
“…We compiled the summary from Dong et al, encompassing all TH deficiency cases reported through 2018 (Dong et al, 2020) and all Segawa patients published thereafter until 2023 (Atanasoska et al, 2023; Bijarnia‐Mahay et al, 2020; Champagne et al, 2022; Chen et al, 2020; Couto et al, 2019; Hou et al, 2019; Hull et al, 2021; Janssen et al, 2021; Kuseyri Hubschmann et al, 2021; Panda et al, 2022; Reyes et al, 2023; Wang et al, 2022). In total, we summarized the clinical phenotypes of all 175 reported Segawa cases.…”
Section: Case Presentationmentioning
confidence: 99%
“…Underdiagnosis is a major issue with THD and differential diagnosis include epilepsy [22], cerebral palsy [22], and vitamin B12-deficiency related infantile tremor syndrome [23] among others. It is important to reach a correct diagnosis at an early stage, as many patients are responsive to treatment.…”
Section: Diagnosing Thdmentioning
confidence: 99%